Data for: Reliability of mechanical ventilation during continuous chest compressions: A crossover study of transport ventilators in a human cadaver model of CPR - Simon Orlob; Christoph Hobisch; Johannes Wittig; Daniel Auinger; Otto Touzil; Gabriel Honnef; Otmar Schindler; Philipp Metnitz; Georg Feigl; Gerhard Prause (Data in Brief, 2023)
The data presented in this article relate to the research article, “Reliability of mechanical ventilation during continuous chest compressions: a crossover study of transport ventilators in a human cadaver model of CPR” [1].This article contains raw data of continuous recordings of airflow, airway and esophageal pressure during the whole experiment. Data of mechanical ventilation was obtained under ongoing chest compressions and from repetitive measurements of pressure-volume curves. All signals are presented as raw time series data with a sample rate of 200Hz for flow and 500 Hz for pressure. Additionally, we hereby publish extracted time series recordings of force and compression depth from the used automated chest compression device. Concomitantly, we report tables with time stamps from our laboratory book by which the data can be sequenced into different phases of the study protocol.We also present a dataset of derived volumes which was used for statistical analysis in our research article together with the used exclusion list.The reported dataset can help to understand mechanical properties of Thiel-embalmed cadavers better and compare different models of cardiopulmonary resuscitation (CPR). Future research may use this data to translate our findings from bench to bedside. Our recordings may become useful in developing respiratory monitors for CPR, especially in prototyping and testing algorithms of such devices.